Using phylogenetics to explore interspecies genetic rescue options for a critically endangered parrot. Issue 9 (26th June 2021) - Hogg, Carolyn J.; Morrison, Caitlin; Dudley, Jessica S.; Alquezar‐Planas, David E.; Beasley‐Hall, Perry G.; Magrath, Michael J. L.; Ho, Simon Y. W.; Lo, Nathan; Johnson, Rebecca N.; Grueber, Catherine E.
Abstract: As the global biodiversity crisis deepens, with increasing habitat fragmentation and a changing climate, innovative options for conserving species are being explored. One such conservation action is genetic rescue: introduction of new alleles to promote population fitness. However, for critically endangered species where only one viable population remains, options for introducing new alleles are limited. Interspecies hybridization offers a potential solution but requires resolution of evolutionary relationships, a sound understanding of species biology, social license, and permissive legislative frameworks. Here, we show how phylogenetics and species biology can inform genetic rescue options for the orange‐bellied parrot (OBP; Neophema chrysogaster ), a critically endangered Australian bird with one small remaining wild population. Our phylogenetic analysis of mitochondrial genomes and nuclear loci for all congeneric species provided strong support for OBPs being the sister species to a group comprising elegant, rock, and blue‐winged parrots. Accounting for species distribution, behavior, and ecology, a captive trial of interspecific hybridization with the blue‐winged parrot is recommended, including assessment of the fitness of hybrid individuals. Introduction of new alleles into the OBP genome would achieve the conservation goal of improving genetic diversity in a critically endangered species. Concurrently, legislative issues will need to be resolved.